2019
DOI: 10.20471/acc.2019.58.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Unicameral Bone Cysts in Children: A Comparative Study

Abstract: Unicameral bone cysts (UBC) are benign bone tumor-like lesions. Mostly they are located in the metaphyseal-diaphyseal region of long bones in children and adolescents. The etiology of UBC is still unclear. There is no consensus about the protocol of UBC treatment. The aim of this study was to evaluate the effectiveness of three different techniques for the treatment of UBC. This study included 129 pediatric patients with UBC treated at University Children's Hospital in Belgrade during the 8-year period. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…El quiste óseo solitario se localiza frecuentemente en la metáfisis de los huesos largos, la evidencia reporta el mayor número de casos aproximadamente el 50 % en el humero proximal, el 20 % en el fémur proximal y muy infrecuentemente se encuentra en el calcáneo específicamente en el cuello del mismo. 10,11 El caso presentado en este artículo coincide con la revisión de la literatura ya que el hallazgo de esta condición patológica es incidental y aunque no pone en riesgo la vida del paciente, al verse afectado considerablemente el hueso calcáneo este puede perder la funcionalidad del miembro inferior ya que causa deformidad e incapacidad.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El quiste óseo solitario se localiza frecuentemente en la metáfisis de los huesos largos, la evidencia reporta el mayor número de casos aproximadamente el 50 % en el humero proximal, el 20 % en el fémur proximal y muy infrecuentemente se encuentra en el calcáneo específicamente en el cuello del mismo. 10,11 El caso presentado en este artículo coincide con la revisión de la literatura ya que el hallazgo de esta condición patológica es incidental y aunque no pone en riesgo la vida del paciente, al verse afectado considerablemente el hueso calcáneo este puede perder la funcionalidad del miembro inferior ya que causa deformidad e incapacidad.…”
Section: Discussionunclassified
“…14 La hidroxiapatita es una alternativa a la utilización de cemento de fosfato de calcio, ambos componentes muestran una gran funcionalidad en periodos de 1 a 5 años con porcentajes altos de curación; sin embargo, la tasa de recurrencia fue sustancialmente más alta en niños menores de 10 años (p=0,01) en quiste activos (p=0,03) (p<0,001) y ubicados en huesos largos (p=0,01) (p<0,001). 15,11 Una nueva estrategia de tratamiento se basa en la utilización hueso diseñado con tejidos como una alternativa al manejo del quiste óseo con hueso alogénico; no obstante, no se han encontrado diferencias significativas entre la aparición de complicaciones y curación ósea (p<0.05). 16…”
Section: Discussionunclassified
“…The range of treatment options includes close observation and activity modification, minimally invasive procedures such as corticosteroid instillation, or surgical evacuation of the cyst by curettage, usually filling the defect with some combination of bone graft, demineralized bone matrix, calcium phosphate or sulfate, or hydroxyapatite. 55 - 57 The choice of intervention must weigh the conflicting priorities of minimizing repetitive fractures by surgically stabilizing fragile cystic bone enabling young patients to partake in normal childhood activities and securing the growth potential of the physis which can be adversely affected by repeated or aggressive curettage.…”
Section: Tumor-like Lesionsmentioning
confidence: 99%
“…39,40 Moreover, some authors demonstrated that a corticosteroid injection offers better results than an isolated bone marrow injection in long-term follow-up studies. 41 Percutaneous intracystic curettage is also a good treatment option, providing better results than an isolated injection. 41 The cyst walls should be treated systematically and perforated to create a communication with the medullary cavity.…”
Section: Simple or Unicameral Bone Cystmentioning
confidence: 99%
“…41 Percutaneous intracystic curettage is also a good treatment option, providing better results than an isolated injection. 41 The cyst walls should be treated systematically and perforated to create a communication with the medullary cavity. The curettage product is aspirated for pathologic examination.…”
Section: Simple or Unicameral Bone Cystmentioning
confidence: 99%